2022
DOI: 10.14742/ajet.7929
|View full text |Cite
|
Sign up to set email alerts
|

Does online engagement matter? The impact of interactive learning modules and synchronous class attendance on student achievement in an immersive delivery model

Abstract: One Australian public university is radically changing the way it delivers higher education, introducing a 6-week immersive scheduling delivery model across all units and courses. Despite the emerging success of block and immersive models for raising the performance of diverse student cohorts, the design factors underpinning positive outcomes are underexplored. This paper presents a mixed methods study of the impact and value of student engagement with interactive and responsive online content modules and sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Some studies found no differences between SDMs and TDMs in terms of academic performance (Ho & Polonsky, 2009;Simunich, 2016), while other studies indicate that SDMs may lead to increased academic performance (Goode et al, 2021;McCluskey et al, 2020;Samarawickrema & Cleary, 2021;Walsh et al, 2019). It appears that the increased academic performance in SDMs may be facilitated by the implementation of active learning pedagogy (Goode et al, 2022;Lee & Horsfall, 2010). Some researchers argue that SDMs reduces cognitive load compared to TDMs, as the competing demands from multiple cognitive demands are reduced in SDMs where students focus on less subjects/tasks/assessments (Goode et al, 2021).…”
Section: Research Gap and Aims Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found no differences between SDMs and TDMs in terms of academic performance (Ho & Polonsky, 2009;Simunich, 2016), while other studies indicate that SDMs may lead to increased academic performance (Goode et al, 2021;McCluskey et al, 2020;Samarawickrema & Cleary, 2021;Walsh et al, 2019). It appears that the increased academic performance in SDMs may be facilitated by the implementation of active learning pedagogy (Goode et al, 2022;Lee & Horsfall, 2010). Some researchers argue that SDMs reduces cognitive load compared to TDMs, as the competing demands from multiple cognitive demands are reduced in SDMs where students focus on less subjects/tasks/assessments (Goode et al, 2021).…”
Section: Research Gap and Aims Of Studymentioning
confidence: 99%
“…To increase engagement and flexibility, the Southern Cross Model offers students two main forms of learning: up to 20 hours of self-assess learning through interactive online learning materials, complemented by three hours of active learning experience in scheduled classes per week. Drawing on cognitive load theory, this SDM reduces the number of concurrent subjects and consequentially allow students to focus on fewer assessments at any one point in time than in the TDM (Goode et al, 2022). Drawing on active learning pedagogy, this SDM requires students to complete media-rich, interactive, and responsive online self-access modules and participate in active, guided experiences in classes.…”
Section: Study Contextmentioning
confidence: 99%
“…Indeed, learning communities have become a necessity in today's digital world for successful learning (e.g., Tegos et al, 2015), and there is a wide body of research which outlines the numerous benefits to student learning. Similarly, Goode et al (2022) report on a mixedmethods study investigating the impact of student engagement with hybrid learning. Findings from the article report that engagement with the online learning component had a positive effect on academic success.…”
Section: Examples Of Lasting Good Practicementioning
confidence: 99%
“…The articles in this special issue have demonstrated that learning principles have remained the same, but the means or methods in which these have been applied have adapted to current trends, and these adaptations have necessitated new support structures and standards. For example, the successes of intensive block learning in online courses in enabling students to focus on one or two units at a time have led to substantial and permanent changes being applied to all courses and all units at some universities, including to traditional face-to-face delivery (Goode et al, 2022).…”
Section: Scaling Online Educationmentioning
confidence: 99%
See 1 more Smart Citation